Studi Literatur: Kebutuhan Pelayanan Kesehatan yang Belum Terpenuhi pada Penyintas Kanker Ginekologi - Sely Kresna Dewi; Marghareta Martini (Jurnal Kesehatan Manarang, 2021)
There is an urgent increase of health care needs for cancer survivor nowadays caused by the escalations of global cancer survivorâ€™s unmet need for cancer care health services. The purpose of this literature study was to identify the gynecology cancer survivorâ€™s unmet need of health care services. A literature search was PRISMA for relevant research paper. Six database were searched: Proquest, Elsevier, Spinger, Wiley Online Library, and Google Scholar using keyword: â€œCaSUNâ€, â€œSCNS-SF34â€, â€œUnmet needâ€,â€ Survivor cancerâ€, â€œSupportive careâ€, Cancer Gynecologicalâ€. The final review included 9 articles from 993 article that being identified from 2015 â€“ 2020. The result of this study was minimum 1 unmet need found in every gynecology cancer survivor, psychological needs and information on health services, physical and sexual needs.